Arnica Montana L. Supercritical Extraction Optimization for Antibiotic and Anticancer Activity - Žitek, Taja; Postružnik, Vesna; Knez, Željko; Golle, Andrej; Dariš, Barbara; Knez Marevci, Maša (Frontiers in Bioengineering and Biotechnology, 2022)
Arnica montana flower heads are known for their antioxidant, antimicrobial and anticancer activity. The aim of this work was to optimize the process of supercritical CO2 extraction, to achieve high extraction yield and high content of biologically active components, and to confirm the antimicrobial and anticancer activity of the extract. The influence of pressure and temperature on the total phenolic content, antioxidant activity, and proanthocyanidin content was evaluated. The pressure and temperature were found to be interdependent. A temperature of 60 °C and a pressure of 300 bar resulted in a high extraction yield, antioxidant activity and phenolic content. The content of proanthocyanidins was highest at a pressure between 180 and 240 bar. The extracts inhibited 3 different microorganisms successfully, S. aureus, E. coli and C. albicans, at concentrations ranging from 0.1 to 5.16 mg/ml, and showed anticancer activity by 85% inhibition of melanoma cell metabolic activity at a concentration of 0.5 mg/ml.